THE EFFECT OF CUE CARDS ON THE SPEAKING ABILITY OF THE EIGHTH GRADE STUDENTS OF SMPN 3 TAMBANG IN DESCRIPTIVE TEXT - Amellya Yusni; Atni Prawati; Marzuki ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out whether there is a significant effect of using cue cards on the speaking ability of the eighth grade students of SMPN 3 Tambang in descriptive text. This is a pre-experimental research conducted by using a pre-test – treatment – post-test design. This research used one group pretest-posttest design. The instrument used in this research was a speaking test in the form of a spoken descriptive text (monologue) for pretest and posttest. The population of this research was 229 of the Eighth Grade Students of SMPN 3 Tambang and the sample of this research is the students from class VIII.1 which is total number of students of class is 33 students. The data of this research were collected by giving a speaking test in the form of a spoken descriptive text (monologue) for pretest and posttest to the students in which the students chose one of the topics about descriptive text and make a description orally. The collected data were analyzed by using t-test formula in SPSS 16.0. The results of data analysis showed the mean score of pretest was 55.79, and the mean score of posttest was 67.95. Based on the data analysis, it can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this research was accepted and null hypothesis was rejected. It also meant that teaching speaking by using cue cards as media was effective to improve students’ speaking ability in descriptive text for the eighth students of SMPN 3 Tambang especially students of class VIII.1.Key Words: Speaking Ability, Cue Cards, Descriptive Text